Bilateral Iris Depigmentation and Ocular Hypotony as End-Stage Manifestations of Untreated Vogt–Koyanagi–Harada Disease (2018)
Purpose: To describe severe bilateral iris depigmentation and persistent ocular hypotony as end-stage manifestations of untreated Vogt–Koyanagi–Harada disease. Methods: We present the clinical findings and diagnostic studies performed for three patients with bilateral iris depigmentation. Results: Vogt–Koyanagi–Harada disease in late recurrent stage was diagnosed in three patients with bilateral severe iris depigmentation and persistent ocular hypotony. Conclusions: Early diagnosis and treatment of inflammation are crucial factors in the clinical outcome of Vogt–Koyanagi–Harada disease. When left undiagnosed and untreated from early stages, severe iris depigmentation and ocular hypotony, uncommon manifestations of this disease, can develop. ©, © Taylor and Francis Group, LLC.